2019
DOI: 10.3390/children6020016
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Coronary Revascularization for Coronary-Artery Obstructive Lesions Due to Kawasaki Disease

Abstract: As an acquired ischemic heart disease in childhood, coronary-artery disease caused by Kawasaki disease (KD) has been known worldwide since the mid-1970s. KD patients who develop coronary-artery obstructive disease often need revascularization some time in their life. Coronary-artery revascularization for KD coronary lesions can be done with the surgical coronary-artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) procedures. However, the characteristics of coronary-arterial lesions cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…Twenty-five year patency has been demonstrated at 87% with IMA grafts vs. 44% for vein grafts. 10 The IMA also deserves particular consideration in children, with its ability to grow in proportion to somatic growth allowing its use from an early age. 10 The same cannot be said for vein grafts or percutaneously placed stents.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five year patency has been demonstrated at 87% with IMA grafts vs. 44% for vein grafts. 10 The IMA also deserves particular consideration in children, with its ability to grow in proportion to somatic growth allowing its use from an early age. 10 The same cannot be said for vein grafts or percutaneously placed stents.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a study conducted in 1988 on 12 patients with LITA-LAD anastomoses reported a 100% patency rate, and the authors found that increases in the length and blood vessel diameter of the LITA paralleled the growth of the children ( 6 ). Recent literature includes reports of CABG involving the GEA, great saphenous vein, and radial artery bypass; most current cases involve the ITA, which is considered the optimal choice for use in bypass surgery in the majority of cases ( 7 – 10 ). Moreover, the use of the ITA requires anastomosis only with the coronary artery, and the minimal difference in the diameters of these vessels facilitates anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, both Kawasaki disease and Kawasaki-like MIS-C are managed similarly, with intravenous immunoglobulin (Ig) and moderate- to high-dose aspirin being the first-line treatments and potential adjuncts including corticosteroids as well as tumor necrosis factor, interleukin (IL)-1, and calcineurin inhibitors and other immunosuppressive agents [ 34 36 ]. Percutaneous coronary intervention and coronary artery bypass grafting are reserved for severe coronary disease, although with potentially improved outcomes [ 37 ].…”
Section: Medium-vessel Vasculitis: Kawasaki Diseasementioning
confidence: 99%